How does climate shock affect technology adoption in rice production? - Thai Phan Nguyen; Duc Kien Nguyen; Quang Dung Truong (Agricultural Economics (AGRICECON))
The objective of the study is to determine the impact of shock from climate change, such as drought and flood, on various technology adoptions in rice production in Vietnam. This study utilised VARHS (The Vietnam Access to Resources Household Survey) panel data from 2012 to 2018 and employed regression analysis following the application of propensity score matching (PSM) to address potential selection bias caused by drought and flood shocks. The findings indicated that households tend to adopt the improved variety of rice and organic fertilisers since households suffer the shock from the drought. Another finding showed that households used more chemical fertiliser and reduced the probability of using improved seeds in rice production since the household was affected by floods. Based on the findings, policies should prioritise promoting and implementing environmentally friendly farming methods that are customised to address specific climate-related difficulties.